Healthcare Work and Organizational Interventions to Prevent Work-related Stress in Brindisi, Italy - Gabriele d'Ettorre; Mariarita Greco (Elsevier, 2015)
Background: Organizational changes that involve healthcare hospital departments and care services of health districts, and ongoing technological innovations and developments in society increasingly expose healthcare workers (HCWs) to work-related stress (WRS). Minimizing occupational exposure to stress requires effective risk stress assessment and management programs. Methods: The authors conducted an integrated analysis of stress sentinel indicators, an integrated analysis of objective stress factors of occupational context and content areas, and an integrated analysis between nurses and physicians of hospital departments and care services of health districts in accordance with a multidimensional validated tool developed in Italy by the National Network for the Prevention of Work-Related Psychosocial Disorders. The purpose of this retrospective observational study was to detect and analyze in different work settings the level of WRS resulting from organizational changes implemented by hospital healthcare departments and care services of health districts in a sample of their employees. Results: The findings of the study showed that hospital HCWs seemed to incur a medium level risk of WRS that was principally the result of work context factors. The implementation of improvement interventions focused on team development, safety training programs, and adopting an ethics code for HCWs, and it effectively and significantly reduced the level of WRS risk in the workplace. Conclusion: In this study HCW resulted to be exposed to occupational stress factors susceptible to reduction. Stress management programs aimed to improve work context factors associated with occupational stress are required to minimize the impact of WRS on workers.